Standardization of functional and regulatory genomic annotation technologies in turbot (Scophthalmus maximus): Applications to improve fish production - Aramburu González, Óscar
Aquaculture production represents an important source of food and employment, turning the sector into a focal point for economic investment to improve production while adressing its core problems, such as diseases. The advances in genomic technologies have opened the door to the disection of the genetic basis and variation that underlies disease resiliance and other productive traits. In this thesis, maps of functional, regulatory and structural elements in the turbot genome were updated and generated. This thesis provides evidence of marks of selection left in the turbot genome throughout its process of domestication and lays out new targets for selection programs by opening the door to the unexplored regulatory elements throught the incorporation of ATAC-Seq and ChIP-Seq technologies.